Faktor risiko diare pada anak usia 1-12 tahun di wilayah kerja Puskesmas II Denpasar Barat, Bali, Indonesia - I Putu Oka Kresna Jayadi; I Made Adi Narendranatha Komara; Made Aditya Artha Nugraha; I Dewa Gede Agung Suta Ariwangsa; Putu Triyasa; I Nengah Kapti (DiscoverSys Inc., 2020)
Background: Diarrhea is a public health problem, with high morbidity and the potential to cause death. A survey conducted from 2000-2010 in Indonesia shows that the incidence of diarrhea is increasing. In Denpasar, diarrhea is one of the top 10 diseases found in Puskesmas. This study aims to determine the risk factors for diarrhea in children aged 1-12 years in the working area of Puskesmas II West Denpasar, Bali, Indonesia.Methods: This study used a case-control analytical method to 86 respondents, which involved 43 children aged 1-12 years with diarrhea for the case and 43 children without diarrhea as a control. This research was conducted from October to December 2017, using consecutive techniques. Data were analyzed using SPSS version 20 for Windows.Results: The results of this study indicate that most of the respondents aged 1-5 years (69.76%) compared to those aged> 5-12 years (30.24%). The percentage of female sex was greater both in the 1-5 years age group (37.20%) and> 5-12 years (18.60 %%) than men. The percentage of bottled water consumption was higher in the control group (79.10%) than in cases (55.80%). There was a significant relationship between diarrhea and environment and hygiene (OR = 5,247; 95% CI: 2,050-13,590; p = 0,000;), hand washing behavior (OR = 4,483; 95% CI: 1,732-12,132; p = 0.002), and food (OR = 3,529; 95% CI: 1,445-8,619; p = 0.005;). However, there was no significant relationship between diarrhea and drinking water sources (OR = 2.246; 95% CI: 0.917-5.504; p = 0.074;).Conclusion: Environmental and hygiene variables, handwashing behavior, and food have a significant relationship with the incidence of diarrhea in children aged 1-12 years in the working area of Puskesmas II Denpasar Barat, Bali, Indonesia.Â Latar Belakang: Diare merupakan salah satu masalah kesehatan masyarakat, dengan angka kesakitan tinggi dan berpotensi menyebabkan kematian. Survei yang dilakukan dari tahun 2000-2010 di Indonesia terlihat kecendrungan insidens diare meningkat. Di Kota Denpasar diare masuk 10 besar penyakit yang dijumpai di Puskesmas. Penelitian ini bertujuan untuk mengetahui faktor risiko diare pada anak usia 1-12 tahun di wilayah kerja Puskesmas II Denpasar Barat, Bali, Indonesia.Metode: Penelitian ini menggunakan metode analitik case-control terhadap 86 responden dimana melibatkan 43 anak berusia 1-12 tahun dengan diare untuk case dan 43 anak tidak menderita diare sebagai control. Penelitian ini dilaksanakan pada bulan Oktober sampai dengan Desember 2017 dengan menggunakan teknik konsekutif. Data dianalisis dengan SPSS versi 20 untuk Windows.Hasil: Hasil penelitian ini menunjukkan bahwa sebagian besar responden berusia 1-5 tahun (69,76%) dibandingkan usia >5-12 tahun (30,24%). Jenis kelamin perempuan secara persentase lebih besar baik pada kelompok usia 1-5 tahun (37,20%) dan >5-12 tahun (18,60%%) dibandingkan laki-laki. Persentase konsumsi air kemasan lebih tinggi pada kelompok kontrol (79,10%) dibandingkan kasus (55,80%). Terdapat hubungan bermakna antara diare dengan lingkungan dan higienitas (OR=5,247; 95% IK: 2,050-13,590; p=0,000;), perilaku mencuci tangan (OR=4,483; 95% IK: 1,732-12,132; p=0,002), serta makanan (OR=3,529; 95% IK: 1,445-8,619; p=0,005;). Akan tetapi tidak terdapat hubungan bermakna antara diare dengan sumber air minum (OR = 2,246; 95% IK: 0,917-5,504; p = 0,074;).Kesimpulan: Variabel lingkungan dan higienitas, perilaku mencuci tangan, maupun makanan memiliki hubungan yang bermakna dengan kejadian diare pada anak usia 1-12 tahun di wilayah kerja Puskesmas II Denpasar Barat, Bali, Indonesia.